2020
DOI: 10.1371/journal.pone.0238843
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis to estimate the healthcare resource utilization and cost associated with treatment-resistant depression in commercially insured US patients

Abstract: The economic burden of commercially insured patients in the United States with treatmentresistant depression and patients with non-treatment-resistant major depressive disorder was compared using data from the Optum Clinformatics™ claims database. Methods Patients 18-63 years on antidepressant treatment between 1/1/13 and 9/30/13, who had no treatment claims for depression 6 months before the index date (first antidepressant dispensing), and who had a major depressive disorder or depression diagnosis within 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…In literature it has been widely reported that TRD patients incur more healthcare expenses and resource use compared to patient with non-TRD depressive syndromes, 9 , 14 and the economic burden significantly increases with the level of resistance. 13 , 15 This tendency was observed in our study as well, by comparing costs over different number of antidepressant lines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In literature it has been widely reported that TRD patients incur more healthcare expenses and resource use compared to patient with non-TRD depressive syndromes, 9 , 14 and the economic burden significantly increases with the level of resistance. 13 , 15 This tendency was observed in our study as well, by comparing costs over different number of antidepressant lines.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Furthermore, TRD patients had higher direct and indirect medical costs than nontreatment-resistant major depressive ones. 9 To the best of our knowledge, there is a lack of data regarding the economic burden of TRD in Italy. In a previous study, we estimated the number of patients affected by TRD in Italy by using selected criteria to identify TRD according to the European Medicines Agency (EMA) definition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the United States Agency for Healthcare Research and Quality, TRD is defined as depression that fails to respond to a minimum of two antidepressant treatments administered at an adequate dose and duration [ 4 ]. Researchers have categorized five stages of TRD: Stage zero is those who have not had a single adequate medication trial; Stage I is a failure of adequate trials of one class of antidepressants; Stage II is a failure of adequate trials of two distinctly different classes of antidepressants; Stage III consists failure of adequate trials of two distinctly different classes of antidepressants and failure to respond to one augmentation strategy, such as lithium or thyroid augmentation; Stage IV consists of all the factors of Stage III and includes the failure to respond to a second augmentation strategy such as monoamine oxidase inhibitors; Stage V has all the aspects of Stage IV along with the failure of an adequate course of electroconvulsive therapy.…”
Section: Reviewmentioning
confidence: 99%
“…From 2010 to 2018, the economic burden of adults with MDD increased by nearly 38%, from $236.6 billion to $326.2 billion [ 3 ]. In 2012 alone, the total burden of MDD exceeded the societal burden of cancer ($131 billion) and diabetes ($173 billion) [ 4 ]. The economic burden associated with MDD comes in part from the treatment methods involved in managing MDD patients.…”
Section: Introductionmentioning
confidence: 99%